Multidisciplinary, minimally invasive approach for oesophageal perforations with delayed presentation - Arvind Kumar; Vikas Singla; Mohan Venkatesh Pulle; Belal Bin Asaf; Harsh Vardhan Puri; Sukhram Bishnoi (Journal of Minimal Access Surgery, 2022)
Background: The present study aims to report the outcomes of a multidisciplinary, minimally invasive approach to treating patients with delayed presentation of oesophageal perforation. Patients and Methods: The present study is a retrospective analysis of prospectively maintained data at a tertiary care centre. All patients with oesophageal perforation presenting over 48 h after the onset of symptoms and without oesophageal obstruction were included in the study. Self-expanding Metallic Stent (SEMS) or endoscopic clip placement was performed in all the patients, followed by video-assisted thoracoscopic surgery (VATS) debridement and decortication of pleural cavity collection. 'Success' was defined as, discharge without the need of oesophageal diversion and complete healing of leak site at 8 weeks with successful removal of the stent. Results: Between March 2012 and December 2019, 12 patients (10 males, median age of 55 years– range of 39–71 years) with oesophageal perforation and delayed presentation underwent treatment with this approach. Ten patients had spontaneous perforation (83.3%) and one patient each had upper gastrointestinal endoscopy-induced and post-traumatic perforation. The median duration of symptoms was 8 days (range 3–31 days). SEMS was placed in ten patients and, in two patients, an over-the-scope clip was used. VATS decortication was done in ten patients (83.3%) and the remaining two (16.7%) underwent VATS debridement. One patient required oesophageal diversion and another patient expired due to sepsis. The overall success with this approach was 83.3%. Conclusion: This multidisciplinary, minimally invasive approach is feasible in patients with thoracic oesophageal perforation and delayed presentation, with a high success rate.